Will "Study in India" be able to build inclusive futures? Preliminary findings from a national survey - Mukherjee, Mousumi; Kumari, Nita (Journal of International Students, 2026)
In many Western countries, the internationalization of higher education is driven by the aim of attracting more full-fee-paying international students. A business model guides this agenda to generate revenue for universities with a steady decline in public funding. In contrast, the recent "Study in India" mission of the Indian government has been driven primarily by the philosophy of "Internationalization at Home," aimed at providing international and intercultural experiences to both domestic and international students. This paper presents preliminary evidence from an ongoing national survey funded by the Indian Council for Social Science Research (ICSSR) to discuss ways to fulfill the "Study in India" mission and build inclusive futures, nurturing global citizens for sustainable development.